Composition and Technology of the 17th Century Stucco Decorations at Červená Lhota Castle in Southern Bohemia. Issue 7 (8th August 2020) - Válek, Jan; Skružná, Olga; Kozlovcev, Petr; Frankeová, Dita; Mácová, Petra; Viani, Alberto; Kumpová, Ivana
ABSTRACT: A high relief stucco decoration from the Great Chamber of the castle Červená Lhota in the Southern Bohemia was surveyed and characterised as a part of its planned conservation. A detailed analytical work was undertaken in order to provide support for the repair works that aimed to be based on a good knowledge of the original materials and application techniques. The main research focus was on the fruit pieces decorating the ribs of vaults. Altogether, over 20 mortar samples were collected from the vault bedding mortar, plaster, stucco elements and the stucco pieces themselves. Additionally, some pieces of stucco (fruits), that were loose and had to be temporarily removed, were studied macroscopically and by X-ray CT. The characterisation of binder, aggregate and additives was carried out using OM, SEM, TA, acid attack, sieve analysis of insoluble residue, XRD, FTIR and nL-MS. It led to an understanding of the uses of various mortar mixes and determination of their composition. The results are discussed as an example of an analytical procedure that aimed at understanding in detail of this historically significant technique from a material and technological standpoint.